These aesthetics are not new: Post-Internet conditions and their effect on contemporary ideas of representation in Painting - Grecia, Callan (Rhodes University, Faculty of Humanities, Department of Fine Art, 2017)
These Aesthetics Are Not New draws inspiration from the effect of digital technological progress on a consumer society. The Internet as a source of ubiquitous imagery reaffirms the idea that in a Post-Internet age there is nothing new, only conditions affected by a networked way of life. In this thesis I attempt to question contemporary ideas of representation and art making, specifically within the medium of oil paint, in a digitally consumed culture of instantaneous access. I interrogate the repetitive imagery that pervades our online experiences, and I speak about how I use my grasp of painterly knowledge and lexicon to replicate digital conditions in the real world to further cement my position that contemporary aesthetics, (digital, physical or both) are not new. I first introduce the reader to the idea of the Post-Internet, exploring the digital's encroachment on our physical spaces and it's relation to the politics of the medium of Oil Paint. I then address the concept of the Image-Object, and unpack this idea by comparing and contrasting emoji's in relation to gestural mark making and the ascription of meaning through iconographic methods in Oil Painting. This culminates in an analysis of my physical practice in relation to these ideas, and concludes with my observations on the future of our ways of seeing, as affected by the Internet and technological progression.
Keywords: Art and the internet; Digital media -- Philosophy; Technology and the arts; Aesthetics; Painting -- Philosophy